Uwarunkowania wprowadzania programów naprawczych w publicznych szkołach wyższych - Pisarska, Aleksandra (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
Universities and colleges prepare financial plans that are their budgets, and are obliged to control the costs, revenues and financial results. This study presents the determinants of preparing reorganization programmes leading to financial balance in public higher education institutions. The authors examined public universities, divided into 10 groups according to the method used by Central Statistical Office in Poland. The paper presents analysis of costs, revenues and financial results of the universities for the years 2007–2011. The analysis of basic dimensions of the universities’ activeness, with special emphasis on the educational and scientific dimension as well as associated with the development of the economic/local community, revealed the problem of too high costs or achieving too low earnings. On one hand, this is probably due to too small expenditures on higher education, on the other hand, because of ineffective use of the university resources. If there is no strict supervision over the level of costs of basic tasks carried out by universities, introducing a recovery programme may, in the future, concern most public universities. It will happen if their core activity (mainly educational) is not brought to balance between revenue and costs.